A Facile Synthesis of a-Hydrazino Ketones from 1,3-Dicarbonyl Compounds Using 1,8-Diazobicyclo[5.4.0]undec-7-ene (DBU) as Organic Catalyst - Rejithamol, R.; Aparna, K.; Swetha, S.; Gayathri, A.; Jisha, S. (Asian Journal of Chemistry, 2017)
a-Hydrazino ketone, 1,3-Dicarbonyl compounds, a-Amination.